Microsoft Transact-SQL : (Jones and Bartlett Publishers, 2011)
"Microsoft Transact-SQL" is a comprehensive guide to the T-SQL language written for the MS SQL Server 2008 developer having performance problems with SQL. The text includes case studies and examples demonstrating how to write or rewrite T-SQL source code